Overexpression of BBX18 Promotes Thermomorphogenesis Through the PRR5-PIF4 Pathway - Hwang, Geonhee; Park, Jeeyoon; Kim, Soohwan; Park, Jeonghyang; Seo, Dain; Oh, Eunkyoo (Frontiers in Plant Science, 2021)
Thermomorphogenesis is the morphological response of plants to an elevation in the ambient temperature, which is mediated by the bHLH transcription factor PIF4. The evening-expressed clock component, PRR5, directly represses the expression of PIF4 mRNA. Additionally, PRR5 interacts with PIF4 protein and represses its transactivation activity, which in turn suppresses the thermoresponsive growth in the evening. Here, we found that the B-box zinc finger protein, BBX18, interacts with PRR5 through the B-Box2 domain. Deletion of the B-Box2 domain abolished the functions of BBX18, including the stimulation of PIF4 mRNA expression and hypocotyl growth. Overexpression of BBX18, and not of B-Box2-deleted BBX18, restored the expression of thermoresponsive genes in the evening. We further show that BBX18 prevents PRR5 from inhibiting PIF4-mediated high temperature responses. Taken together, our results suggest that BBX18 regulates thermoresponsive growth through the PRR5-PIF4 pathway.